An evaluation of the automated assay of urinary oestrogens in pregnant women. Issue 6 (September 1970) - Muir, G. G.; Ryan, M.; Conaill, D. U.
Abstract : An automated assay suitable for estimating urinary oestrogens in pregnant women has been investigated. Fluorimetry was found to have considerable advantages over colorimetry. The fluorimetric assay was simpler, more precise, more sensitive, and eliminated the need for correction for non-specific chromogens; in the assay of oestriol in pregnant women there was no need for correction for non-specific fluorescence. Spectrofluorimetric and photometric analyses, recoveries, and reproducibility show that the method offers a robust means of providing values for urinary oestrogen in pregnant women on a scale of up to 100 tests a day, the time of the assay being one and a half hours.